Black and White individuals differ in dementia prevalence, risk factors, and symptomatic presentation. Issue 8 (2nd December 2021) - Lennon, Jack C.; Aita, Stephen L.; Bene, Victor A. Del; Rhoads, Tasha; Resch, Zachary J.; Eloi, Janelle M.; Walker, Keenan A.
Abstract: Introduction: Although dementia prevalence differs by race, it remains unclear whether cognition and neuropsychiatric symptom severity differ between Black and White individuals with dementia. Methods: Using National Alzheimer's Coordinating Center (NACC) data, we evaluated dementia prevalence in non‐Hispanic Black and White participants and compared their clinicodemographic characteristics. We examined race differences in cognition, neuropsychiatric symptoms, and functional abilities in participants with dementia using multivariable linear and logistic regression models. Results: We included 5, 700 Black and 31, 225 White participants across 39 Alzheimer's Disease Research Centers. Of these, 1, 528 (27%) Black and 11, 267 (36%) White participants had dementia diagnoses. Despite having lower dementia prevalence, risk factors were more prevalent among Black participants. Black participants with dementia showed greater cognitive deficits, neuropsychiatric symptoms/severity, and functional dependence. Discussion: Despite lower dementia prevalence, Black participants with dementia had more dementia risk factors, as well as greater cognitive impairment and neuropsychiatric symptom severity than White participants.